Among Ruins - Gibb, Robert, 1946- (Book collections on Project MUSE., 2017)
Among Ruins is the final volume of Homestead Works, a collection of four books of poetry that explore the industrial past and legacy of the old steel town of Homestead, Pennsylvania, and, by extension, Pittsburgh.